Factors behind Third-Party Logistics Providers Readiness towards Halal Logistics - Hazwani Ahmad Tarmizi; Nitty Hirawaty Kamarulzaman; Ismail Abd Latiff; Azmawani Abd Rahman (International Journal of Supply Chain Management, 2014)
Halal logistics is an approach to avoid contamination of perishables, raw materials, and food products during distribution activities taking into consideration the need for Halalan toyibban products for consumption by Muslim consumers. The Malaysian Standard for Halal Logistics (MS 2400:2010) provides the guidelines on halal logistics based on the Shariah law, for logistics providers to specialize in transportation, warehousing, and retailing. The requirements for halal logistics involve specifications throughout processing, handling, distribution, storage, display, serving, packaging, and labelling of the products. There are concerns on logistics providers meeting the required standards on halal logistics implementation. This study thereby strives to investigate factors that influence halal logistics implementation among food-based logistics providers. Face-to face interviews were carried out with 156 managerial representatives of logistics companies located in Peninsular Malaysia. Descriptive analysis was used for company profiling, while factor analysis and logistics regression analysis were carried out to determine influential factors to halal logistics implementation among the logistics providers. Support from management, enforcement of Halal Assurance System (HAS), environment controls, employee acceptance, and company vision to change are the factors identified influencing halal logistics implementation among logistics providers.